2015
DOI: 10.1111/cdoe.12153
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal contribution to intergenerational psychosocial transmission of paan chewing

Abstract: ABSTRACT:Objectives: Paan chewing is a recognized risk factor for oral cancer in the Asian population. However, there is currently little evidence about the intergenerational psychosocial transmission of paan chewing in South Indian families. We investigated the association between parental and participant's paan chewing in a South Indian population.Methods: A subset of data was drawn from a hospital-based case-control study on oral cancer, the HeNCe Life study, conducted at Government Dental and Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Cases are likely to smoke or chew nearly four times more when their parents had a history of Tobacco use as opposed to controls. This intergenerational transfer has been studied in western societies (Madathil et al, 2015;Mahabee-Gittens et al, 2012;Vandewater et al, 2014;Vuolo and Staff, 2013;White et al, 2000) and similar strong associations have been found. The findings of our study show the risk of transfer of smoking habits from a parent to a smoker case to be nearly three times when compared to a control [OR 2.79 (95%CI 1.85 -4.19.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Cases are likely to smoke or chew nearly four times more when their parents had a history of Tobacco use as opposed to controls. This intergenerational transfer has been studied in western societies (Madathil et al, 2015;Mahabee-Gittens et al, 2012;Vandewater et al, 2014;Vuolo and Staff, 2013;White et al, 2000) and similar strong associations have been found. The findings of our study show the risk of transfer of smoking habits from a parent to a smoker case to be nearly three times when compared to a control [OR 2.79 (95%CI 1.85 -4.19.…”
Section: Discussionsupporting
confidence: 61%
“…This finding has been seen consistently across all ethnic groups (Hoskins, 2014). Madathil et al, (2015) concluded maternal strictness was associated with decreased Tobacco uptake by the child. Though our study findings are distinct from the previous study, it is of substantial significance, as unlike the traditional concept of mother's central role in the rearing of a child; our study results highlight the father's role in the process of parenting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Covariates included lifetime history of paan chewing, bidi and cigarette smoking, alcohol consumption, age, sex and years of education. 31 In brief, the lifetime consumption of paan was calculated for participants who reported chewing paan for at least one year at any point in their lives, classified as ever chewers. To obtain a comprehensive history of paan chewing, we asked the subjects to describe their habit by dividing their lifetime consumption into periods based on the homogeneity of paan composition and frequency of use.…”
Section: Discussionmentioning
confidence: 99%